FREEDOM OF INFORMATION AND THE RIGHT TO ENVIRONMENTAL PROTECTION - Carvalho, Ana Cristina (European Scientific Journal, ESJ, 2015)
Freedom of information is essential to exercise the right to environmental protection, which belongs to all people in the world and deserves a special attention as they will not be able to exercise it without access to environmental information. The United Nations Human Rights Council adopted a resolution on human rights and climate change, which calls for increased international dialogue on the adverse impacts of climate change with an emphasis on those States with the greatest need of assistance from the international community. However, the effective environmental protection is only possible through the active participation of the public, so citizens should be enabled to take their own responsibility for the environment more seriously. In this sense, the Aarhus Convention stipulates important rights for the participation of citizens in environmental protection and establishes a number of rights of the public (individuals and their associations) with regard to the environment. This paper aims to analyze whether international law can help to promote the access to environmental information in an efficient way. The adopted methodology comprehends a deductive approach and techniques of qualitative, theoretical, explanatory and bibliographic research, by consulting books, websites, journal articles, news and official documents. The results show a critical view of the current rules and propose suggestions on how the issue of access to environmental information should be addressed in order to benefit the whole international community by promoting access to world’s environmental information.